Mitchellville: a study of the adaptation responses of women in prison - Jones, Richard Statler (1986)
This study is a descriptive analysis of the prison experience of female inmates in the Iowa Correctional Institution for Women at Mitchellville. Data for this study were collected and analyzed through a qualitative methodological approach. Prior research on women prisoners indicates that female inmates tend to organize into relatively enduring primary relationships, often involving dyadic homosexual attachments and extensive kinship networks. The present study examined a number of dimensions of the prison experience, including the fears and expectations that inmates had about prison before their arrival at Mitchellville; the change in the inmate's definition of the situation through her early participation in prison; the inmate's perceptions of the deprivations of incarceration; how inmates respond to the deprivation of incarceration; and the impact that relationships outside of prison have on the inmate's response to incarceration. What emerges from this study is that three primary modes of adaptation develop at Mitchellville in response to the pains of incarceration: quasi-families, couples, and rap-partnerships